Francisco López de Gómara's General history of the Indies - Lehmann, Clayton Miles, translator; Helmer, Ángela, translator; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
This work is the first English translation of the entire text of part one of sixteenth-century Spanish historian Francisco López de Gómara's The General History of the Indies. This translation expands the archive of texts available to English-speakers reconsidering the various aspects of the European invasion of America.--Provided by publisher.
Historia general de las Indias. Hispania victrix
Keywords: America -- Discovery and exploration -- Spanish -- Early works to 1800; America -- Discovery and exploration -- Spanish -- Sources; Latin America -- History -- To 1600 -- Early works to 1800; America -- Early accounts to 1600